2018
DOI: 10.1111/jonm.12666
|View full text |Cite
|
Sign up to set email alerts
|

Perceived career opportunities, commitment to the supervisor, social isolation: Their effects on nurses’ well-being and turnover

Abstract: Aim This research investigated the relationship between perceived career opportunities, affective commitment to the supervisor, and social isolation from colleagues on the one hand and nurses’ well‐being and turnover intentions on the other. In addition, this study explored the mediating role of affective commitment to the organisation in these relationships. Background Previous research suggested that organisational commitment explained the effect of nurses’ work environment on their turnover intentions. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…Moreover, research has shown that affective commitment toward the organization acts as a mediating variable between affective commitment to the supervisor and turnover intention (Panaccio and Vandenberghe, 2011;Huyghebaert et al, 2019). Therefore, in line with previous hypotheses, the moderating effect of PSSP in the relation between affective commitment to the supervisor and the organization should have an indirect effect on turnover intention.…”
Section: The Moderating Role Of Pssp In the Relation Between Commitmesupporting
confidence: 65%
“…Moreover, research has shown that affective commitment toward the organization acts as a mediating variable between affective commitment to the supervisor and turnover intention (Panaccio and Vandenberghe, 2011;Huyghebaert et al, 2019). Therefore, in line with previous hypotheses, the moderating effect of PSSP in the relation between affective commitment to the supervisor and the organization should have an indirect effect on turnover intention.…”
Section: The Moderating Role Of Pssp In the Relation Between Commitmesupporting
confidence: 65%
“…Furthermore, various methods have been proposed to address or prevent this problem, since nursing managers either directly or indirectly exert a major influence on the quality of care provided to patients [29,39]. It has been suggested that changes should be made in how duties are organized.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Harman's single factor test (Schriesheim, 1979) is used to statistically address the common method variance issues. This test has been widely accepted and used to assess common method biases by contemporary healthcare researchers when conducting studies in nursing and healthcare (Huyghebaert, Gillet, Audusseau, & Fouquereau, 2019;Nguyen, Teo, Pick, & Jemai, 2018), despite the criticisms (Min, Park, & Kim, 2016). We used exploratory factor analysis (Podsakoff, MacKenzie, Lee, & Podsakoff, 2003).…”
Section: Common Methods Biasesmentioning
confidence: 99%